Strategi Penghimpunan dan Penyaluran Dana pada Baitul Maal Wat Tamwil (BMT) al-Hidayah di Kabupaten Lombok Timur - Sanwani Sanwani; Titiek Herwanti; Akhmad Jufri (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2017)
The purpose of this study was to determine the strategies used in collecting and distributing funds on Baitul Maal wat Tamwil (BMT) al-Hidayah in East Lombok. Reason investigated, because the collection and distribution of funds strategy in BMT al-Hidayah which shows the development and BMT relative age of 10 years old, BMT al-Hidayah also have extensive cooperation network. Based on the above reasons researchers assume that the collection and distribution of funds strategy in BMT al-Hidayah was nice because the researchers wanted to know how the collection and distribution of funds strategy BMT al-Hidayah. This research was conducted with a qualitative approach, the process using triangulation techniques as collecting data and analyzing the results. Focus of this study was to determine the strategies used in collecting and distributing funds on Baitul Maal wat Tamwil (BMT) al-Hidayah in East Lombok. Results of research on how the collection and distribution of funds strategy in BMT al-Hidayah which are coming directly to the place of prospective customers, social care, marketing, and promotion of the brochures that were disseminated to the public.